ADDRESSING CROSS- BORDER DATA ACCESS FOR EFFECTIVE LAW ENFORCEMENT - Das, Shruti; Sagar, Sarika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Online data is increasingly used by law enforcement to obtain evidence for investigations. Accessing this data, especially from cloud-based services, is difficult due to jurisdictional issues and changing technology. This article examines how cloud computing, data protection legislation, and multinational collaboration affect law enforcement agencies’ cross-border data access. Extraterritorial data access legislation in the U.S. and EU pose accountability and transparency concerns, especially in liberal democracies. The study discusses private sector monitoring, corporate social responsibility programs including transparency reports, and state-corporate surveillance issues. In India, law enforcement agencies increasingly use cross-border data access but struggle with delayed and complicated mutual legal assistance treaties (MLATs) and Letters Rogatory (LRs). Tech company transparency reports show that data disclosure policies and regulatory requirements vary, with India failing to get vital evidence. The article continues by examining India’s emerging data governance structure, including privacy, cross-border transfers, and law enforcement access issues. To secure data governance and security in an increasingly linked world, clearer legislation, increased international cooperation, and global best practices are needed